1996
DOI: 10.1093/jac/38.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of in-vitro activity and pharmacokinetic parameters with in-vivo effect of amoxycillin, co-amoxiclav and cefotaxime in a murine model of pneumococcal pneumonia

Abstract: In an attempt to determine the susceptibility breakpoints for amoxycillin, co-amoxiclav and cefotaxime in pneumococcal pneumonia, a neutropenic mouse model was established and tested with two strains having different susceptibility to penicillins and cefotaxime. With a penicillin-sensitive strain (MIC/MBC = 0.01/0.01 mg/L) the minimum dosage tested achieving significant cure was 2 mg/kg for amoxycillin, co-amoxiclav and cefotaxime. For the penicillin-insensitive strain (MIC/MBC = 1/2 mg/L), the minimum dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…They have widely been used for analyzing pathogenicity mechanisms of pneumonia (50,58,114,120,125,131), sepsis (109,131,251), and meningitis (59,95,160,268). In addition, outbred mice have also been employed to evaluate active and passive protection against pneumonia and sepsis (4, 115, 163) and the efficacy of antibiotic therapy against invasive pneumococcal disease (13,141,169,220,223). The host genetic factors controlling the response to infection by S. pneumoniae are still unknown.…”
Section: Considerations Of Animal and Pneumococcal Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have widely been used for analyzing pathogenicity mechanisms of pneumonia (50,58,114,120,125,131), sepsis (109,131,251), and meningitis (59,95,160,268). In addition, outbred mice have also been employed to evaluate active and passive protection against pneumonia and sepsis (4, 115, 163) and the efficacy of antibiotic therapy against invasive pneumococcal disease (13,141,169,220,223). The host genetic factors controlling the response to infection by S. pneumoniae are still unknown.…”
Section: Considerations Of Animal and Pneumococcal Strainsmentioning
confidence: 99%
“…Typically, strains of capsular serotypes 2, 3, 4, 5, and 6 are virulent in mice, whereas strains of types 14, 19, and 23 are relatively avirulent (21,39). The low virulence of many pneumococcal strains in rodents can be balanced by either using larger challenge doses (40) or neutropenic hosts (19,49,169,221,223).…”
Section: Considerations Of Animal and Pneumococcal Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50% effective dose (ED 50 ; the single dose giving protection to 50% of the mice) was determined from two trials by the Probit method (5). In the first trial, drugs were given in 10-fold dilutions of 0.1 to 100 mg/kg to six mice in each treatment group (7,14,15).…”
mentioning
confidence: 99%
“…The doses selected for amoxicillin administration were based on the results from a previous study by our group [26] which showed that the maximum amoxicillin concentrations attained in mouse serum after single doses of amoxicillin of 200 mg/kg and 50 mg/kg were 300 mg/L and 75 mg/L, respectively. However, such high amoxicillin concentrations cannot be achieved in patients following oral administration of usual dosages.…”
mentioning
confidence: 99%